Directory of members legislative offices of the Senate and the House of Representatives, ninth Philippine Congress. (Quezon City Congressional Research and training Service, Inc., 1992)
To help the various groups and individuals facilitate greater access to the offices of the members of the 9th congress, the Congressional Research and Training Service has compiled this directory. For the House of Representatives, the names of the members are listed alphabetically with the corresponding entries: room number, local and direct line, province/district, names of the Chiefs of Staff, and private secretaries or contact persons. In the case of the senate, the following entries were included: office address, telephone numbers, and fax/telex numbers, names of Chiefs of Staff and of secretaries.
Cover title.
Keywords: Philippines. -- Congress. -- House of Representatives -- Directories; Philippines. -- Congress. -- Senate -- Directories; Legislators -- Philippines -- Directories